Taxonomies of Business Performance Management Solutions - Januszewski, Arkadiusz (Advanced Information Technologies for Management – AITM 2009, 2009)
The main aim of the paper is to present taxonomies of Business Performance Management (BPM) software. BPM software supports strategy and performance management. The market of BPM software is still growing and this software category is becoming more and more important for managers and companies. The world-wide known consultant groups, such as IDC, Gartner and Forester Research, give various definitions of BPM software and categorize the software packages in different ways. The author presents these definitions and taxonomies, as well as tries to indicate their common features.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 85, s. 118-125